Defamatory meanings and the hazards of relying on the ‘ordinary, reasonable person’ fiction - Fernandez, Joseph (Pacific Media Centre, AUT, 2017)
© 2017, Pacific Media Centre, Auckland University of Technology. All rights reserved. Defamation law offers a remedy when the plaintiff’s reputation is harmed by something the defendant publishes. At the heart of the action lies the question—what do the words complained about actually mean? The process of determining defamatory meaning depends heavily on what the court finds to be the imputations conveyed by the matter concerned to ‘ordinary, reasonable people’. The process relies on assumption and conjecture, rather than on evidence. This article examines how this process applied in the Hockey v Fairfax Media case brought by Australia’s former Federal Treasurer Joe Hockey against Fairfax Media, which presented a paradox—the court described the journalists’ articles concerned in glowing terms but still found for the plaintiff.